Shouting at each other into the void: A linguistic network analysis of vaccine hesitance and support in online discourse regarding California law SB277. (December 2020) - DeDominicis, Kali; Buttenheim, Alison M.; Howa, Amanda C.; Delamater, Paul L.; Salmon, Daniel; Omer, Saad B.; Klein, Nicola P.
Abstract: In 2015, California passed Senate Bill 277 and became the third state in the United States to ban all nonmedical exemptions from school immunization requirements, effectively prohibiting religious and personal belief exemptions. This attracted grassroots opposition and considerable debate among vaccine hesitant factions online. This mixed-methods study used quantitative linguistic analysis, semantic network analysis, and content analysis techniques to examine 2424 online documents drawn from newspapers, blogs, health websites, government information pages, web forums, personal websites, Facebook groups, among others. The study examined which words and phrases were used most frequently by vaccine skeptics, vaccine defenders, and more neutral media accounts to illuminate how groups with different attitudes towards vaccination discuss and disseminate information about vaccines and vaccine policy online. We proposed an innovative methodology for examining online discourse surrounding vaccine hesitance, as well as for studying the online dissemination of misinformation about vaccines. Our findings highlighted discrepancies in the narratives between what vaccine supporters believe causes vaccine skepticism and the issues that vaccine skeptics actually discuss within their own digital spaces. For example, in these exchanges, the importance of parental rights overshadowed that of children's rights; supporters of vaccines brought up autism in more distinct documents than skeptics do; distrust of government regulators and researchers seemed to unite vaccine skeptics and defenders; and politicians, doctors, and even celebrities often served as proxies in heated exchanges about factual evidence, believability, and the importance of expertise in public discourse. Highlights: Explores online discussions of vaccines and vaccine mandates, specifically California SB277. Modifies snowball sampling to reflect digital infrastructure, online information. Semantic Network Analysis used to illuminate narratives around vaccine skepticism. Challenges current understandings of vaccine skeptic coalition and priorities. Useful for doctors and policymakers seeking to convince vaccine skeptical parents.